Influence of Inclination Angle at the Chimney Inlet on the Power Generation in Solar Chimney Power Plants through 3D CFD Model - Mahmut Kaplan (International Journal of Photoenergy)
The sun is an abundantly available and clean renewable energy source. Therefore, solar energy offers significant potential for mitigating climate change and reducing emissions from burning fossil fuels in the future. Solar chimney power plants (SCPPs) have a technical capability for meeting the massive sustainable power production. Basic parts of SCPP system are the chimney, turbine, and collector. The geometric dimensions of the components are the crucial factors for improving the solar chimney efficiency. The goal of this work is to analyse the influences of the inclination angle (θ) at chimney inlet on performance characteristics of the system by employing RNG k−ε turbulence model coupled with discrete ordinate (DO) solar ray tracing method via ANSYS Fluent CFD software. The model is built by taking into consideration geometric parameters of Manzanares plant and verified with its measurements. The innovative chimney entrance configurations are produced by altering the chimney entrance slope (θ=50°–80°) with the geometrical dimensions of the chimney, collector, and fillet keeping constant. The computational results display that the new chimney configurations improve the maximum velocity, system power output, and turbine pressure drop. The peak velocity of 18.1 m/s is gained for the configuration with θ=80° compared to that of 14.3 m/s obtained for the base model having θ=45° at 1000 W/m2. Besides, this configuration enhances power output to 61.5 kW with a rise of 24.5% compared to the base model with a power output of 49.1 kW at 1000 W/m2.